2021
DOI: 10.3389/fpls.2021.696045
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Morphological Responses of Hydroponically Grown Pear Rootstock Under Phosphorus Treatment

Abstract: Phosphorus (P) is an essential macronutrient for the growth and development of fruit trees, playing an important role in photosynthesis, nucleic acid synthesis, and enzyme activity regulation. The plasticity of plant phenotypic has been investigated in diverse species under conditions of P-deficiency or P-excess. Based on these researches, P level fluctuations in different species result in different characteristics of the response. Nevertheless, little is known about the response of pear seedling rootstock (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Consistent with these findings, the present study demonstrates a significant reduction in total root length, total root surface area, and total root volume, excluding total root diameter, under deficient or low P conditions (Table 1). This underscores the plasticity of the root system architecture, likely influenced by P deficiency's impact on the carbon budget (Chen et al, 2021). Physiological plasticity plays a crucial role, primarily in optimizing the uptake of mobile ions, particularly nitrate.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these findings, the present study demonstrates a significant reduction in total root length, total root surface area, and total root volume, excluding total root diameter, under deficient or low P conditions (Table 1). This underscores the plasticity of the root system architecture, likely influenced by P deficiency's impact on the carbon budget (Chen et al, 2021). Physiological plasticity plays a crucial role, primarily in optimizing the uptake of mobile ions, particularly nitrate.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that a deficiency of phosphorus can result in a decrease in leaf number, reduced leaf area, alteration of root/shoot biomass and stunted plant growth. [2][3][4] For instance, phosphorus deficiency (<0.5 mM) in pear plants has a significant effect on root morphology and growth, but the exact effect depends on the plant species. 2 However, excess phosphorus (>5 mM) can also lead to delayed flowering and dark colored leaves in pear plants.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] For instance, phosphorus deficiency (<0.5 mM) in pear plants has a significant effect on root morphology and growth, but the exact effect depends on the plant species. 2 However, excess phosphorus (>5 mM) can also lead to delayed flowering and dark colored leaves in pear plants. 2 Furthermore, the requirement for phosphorus varies depending on the plant and the growing methods, like aquaponics needing less phosphorus compared to hydroponics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations